Simulation on the roles of the number of quantum well and doping in InxGa1-xN Multiple Quantum Wells LEDs - Zainal, N.; Azimah, E.; Hassan, Z.; Abu Hassan, H.; Hashim, M.R. (Universiti Kebangsaan Malaysia, 2014)
In this work, the emission efficiency of InxGa1-xN based light emitting diodes (LEDs) had been numerically investigated with the variation of the number of quantum well. From our calculation, we found that non-uniformity of carriers distribution (especially electron) in the wells leads to serious inhomogeneity of radiative recombination distribution that would degrade the efficiency of the LED with more wells. However, the problem was minimized when the selected quantum barriers were doped with a reasonable doping level. Comparison with other reported experimental works were also included. At the end of this work, we proposed several types of preferable LEDs designs with optimum structural parameters.